2020
DOI: 10.1159/000508919
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dialysis Metrics and Patient-Reported Cognition, Fatigue, and Physical Function

Abstract: Introduction: The impact of achieving hemodialysis laboratory and hemodynamic quality metrics on patient-reported outcomes (PROs) is unknown. Objective: To determine if meeting dialysis laboratory quality of care measures is associated with improved PROs. Methods: In this cross-sectional study, we measured the relationship between dialysis patients' Patient Reported Outcome Measurement Information System (PROMIS) scores and commonly used dialysis quality of care measures. Results: PROMIS surveys were administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Patients on hemodialysis with comorbidities often experience fatigue, and a positive correlation between exercising for less than 1 h daily and fatigue was identified [ 56 ]. However, few studies have explored whether Kt/V scores and anxiety are correlated [ 57 ]. Hornik et al [ 58 ] reported that relative to patients on hemodialysis who engaged in a low level of physical activity on an irregular basis, those who engaged in a high level of physical activity on a regular basis have a lower comorbidity rate; their study also posited that regular physical activity improves the effect of hemodialysis on patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on hemodialysis with comorbidities often experience fatigue, and a positive correlation between exercising for less than 1 h daily and fatigue was identified [ 56 ]. However, few studies have explored whether Kt/V scores and anxiety are correlated [ 57 ]. Hornik et al [ 58 ] reported that relative to patients on hemodialysis who engaged in a low level of physical activity on an irregular basis, those who engaged in a high level of physical activity on a regular basis have a lower comorbidity rate; their study also posited that regular physical activity improves the effect of hemodialysis on patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown a relationship between PDF and sociodemographic factors such as age, gender and employment status; medical problems such as anaemia, malnutrition, sleep disorders and secondary hyperparathyroidism; changes in clinical variables such as albumin, Kt/V and the urea reduction rate; and psychological conditions such as anxiety, stress and depression 7,11,12 …”
Section: Introductionmentioning
confidence: 99%
“…10 Various studies have shown a relationship between PDF and sociodemographic factors such as age, gender and employment status; medical problems such as anaemia, malnutrition, sleep disorders and secondary hyperparathyroidism; changes in clinical variables such as albumin, Kt/V and the urea reduction rate; and psychological conditions such as anxiety, stress and depression. 7,11,12 There is no consensus decision or a specific diagnostic tool with proven validity and reliability as regards defining PDF and its severity. 5,9 Although the vitality subdimension of the SF-36 QoL Scale and the Visual analogue scale (VAS) are frequently used in the relevant studies, 5,13 it is not possible to define the severity and incidence of PDF.…”
mentioning
confidence: 99%
“…Further, PROMIS domains demonstrated greater reliability over a broader range of symptom severity or functional impairment compared with SF-12 or SF-36 (31,32). The precise, versatile PROMIS item banks (administered either as four-or eight-item short forms, or computer adaptive test) have also already been used as outcome measures studies (33,34) and in clinical practice for symptom monitoring (35)(36)(37). In addition, PROPr, and the overall mental and physical health summary scores (38), provide reliable measures of health utility and overall HRQOL.…”
Section: Discussionmentioning
confidence: 99%